EFEKTIVITAS SANKSI PIDANA BAGI PELANGGARAN TINDAK PIDANA PEMILU - Rizka Amaliatus Syafaah (MASADIR: Jurnal Hukum Islam, 2023)
In Indonesia, violations of election crimes are not something new. In fact, violations of election crime are almost always found in every election period that take place. During the last election period in 2019 to be exact, there were around 548 findings and reports of election crimes that reached the court examination stage. And in the previous period (2014 election) there were also around 70 findings of criminal violations. Even though there are regulations and sanctions that strictly regulate this matter, these violations still occur. This Article aims to analyze empirically regarding the effectiveness of criminal sanction for violations of election crimes. The research method used in this research is empirical research, where this research focuses on harmony between the reality that occurs in society and existing laws. This study concludes that the effectiveness of criminal sanction as a tool to evercome the occurrence of election crimes cannot be properly practiced if they are not supported by the existence of legal awareness in society, the legal culture that exists in society and a sense of nationalism in order to achieve honest, clean and fair election, fair and not concerned with power and victory alone.